Enzymatic degradation of thiolated chitosan. (October 2013) - Laffleur, Flavia; Hintzen, Fabian; Rahmat, Deni; Shahnaz, Gul; Millotti, Gioconda; Bernkop-Schnürch, Andreas
Abstract : The objective of this study was to evaluate the biodegradability of thiolated chitosans in comparison to unmodified chitosan. Mediated by carbodiimide, thioglycolic acid (TGA) and mercaptonicotinic acid (MNA) were covalently attached to chitosan via formation an amide bond. Applying two different concentrations of carbodiimide 50 and 100 mM, two chitosan TGA conjugates (TGA A and TGA B) were obtained. According to chitosan solution (3% m/v) thiomer solutions were prepared and chitosanolytic enzyme solutions were added. Lysozyme, pectinase and cellulase were examined in chitosan degrading activity. The enzymatic degradability of these thiomers was investigated by viscosity measurements with a plate–plate viscometer. The obtained chitosan TGA conjugate A displayed 267.7 µmol and conjugate B displayed 116.3 µmol of immobilized thiol groups. With 325.4 µmol immobilized thiol groups, chitosan MNA conjugate displayed the most content of thiol groups. In rheological studies subsequently the modification proved that chitosan TGA conjugates with a higher coupling rate of thiol groups were not only degraded to a lesser extent by 20.9–26.4% but also more slowly. Chitosan mercaptonicotinic acid was degraded by 31.4–50.1% depending the investigated enzyme and even faster than unmodified chitosan. According to these results the biodegradability can be influenced by various modifications of the polymer which showed in particular that the rate of biodegradation is increased when MNA is the ligand, whereas the degradation is hampered when TGA is used as ligand for chitosan.